Humans in XAI: Increased Reliance in Decision-Making Under Uncertainty by Using Explanation Strategies - Lammert, Olesja; Richter, Birte; Schütze, Christian; Thommes, Kirsten; Wrede, Britta (Frontiers in Behavioral Economics)

Time perspectives and collaborative performance in creative tasks - Auer, Thorsten Fabian; Hoppe, Julia Amelie; Thommes, Kirsten (Journal of Organizational Effectiveness: People and Performance)
Purpose The relationship between variation in time perspectives and collaborative performance is scarcely explored, and even less is known about the respective mechanisms that lead to varying task performance. Thus, we aim to further the literature on time perspectives and collaborative performance, shedding light on the underlying behavioral patterns. Design/methodology/approach We report a quasi-experiment analyzing the impact of past, present and future orientation variation in dyads ( N = 76) on their quantitative and qualitative performance when confronted with a simple incentivized creative task with constraints. Subsequently, we offer a qualitative analysis of comments given by the participants after the task on the collaboration. Findings Results indicate that a dyad's elevation of past orientation and diversity in future orientation negatively affect collaborative performance. At the same time, there is a positive effect of elevation of future orientation. The positive effect is driven by clear communication and agreement during the task, while the negative effect arises from work sharing and complementation. Practical implications This study provides insights for organizations on composing individuals regarding their temporal focus for collaborative tasks that should be executed rapidly and require creative solutions. Originality/value Our study distinguishes by considering the composition of past, present and future time perspectives in dyads and focuses on a creative task setting. Moreover, we explore the mechanisms in the dyads with a substantial elevation of/diversity in future orientation, leading to their stronger/weaker performance.
Keywords: Organizational Behavior and Human Resource Management

Can leaders motivate employees’ energy-efficient behavior with thoughtful communication? - Hoffmann, Christin; Thommes, Kirsten (Journal of Environmental Economics and Management)
Keywords: Management; Monitoring; Policy and Law; Economics and Econometrics

Are Numbers or Words the Key to User Reliance on AI? - Papenkordt, Jörg; Ngonga-Ngomo, Axel-Cyrille; Thommes, Kirsten (Academy of Management Proceedings)

Aggregating Human Domain Knowledge for Feature Ranking - Kornowicz, Jaroslaw; Thommes, Kirsten (Artificial Intelligence in HCI)